Procoagulant Phospholipids and Tissue Factor Activity in Cerebrospinal Fluid from Patients with Intracerebral Haemorrhage - Patrick Van Dreden; Guy Hue; Jean-François Dreyfus; Barry Woodhams; Marc Vasse (Advances in Hematology)
Brain contains large amounts of tissue factor, the major initiator of the coagulation cascade. Neuronal apoptosis after intracerebral haemorrhage (ICH) leads to the shedding of procoagulant phospholipids (PPLs). The aim of this study was to investigate the generation of PPL, tissue factor activity (TFa), and D-Dimer (D-Di) in the cerebrospinal fluid (CSF) at the acute phase of ICH in comparison with other brain diseases and to examine the relationship between these factors and the outcome of ICH. CSF was collected from 112 patients within 48 hours of hospital admission. Thirty-one patients with no neurological or biochemical abnormalities were used to establish reference range in the CSF (“controls”). Thirty had suffered an ICH, and 51 other neurological diagnoses [12: ventricular drainage following brain surgery, 13: viral meningitis, 15: bacterial meningitis, and 11 a neurodegenerative disease (NDD)]. PPL was measured using a factor Xa-based coagulation assay and TFa by one home test. PPL, D-Di, and TFa were significantly higher (P<0.001) in the CSF of patients with ICH than in controls. TFa levels were significantly (P<0.05) higher in ICH than in patients with meningitides or NDD. Higher levels (P<0.05) of TFa were observed in patients with ICH who died than in survivors. TFa measurement in the CSF of patients with ICH could constitute a new prognostic marker.